Availability and Utilization of IPAS Learning Media in Fourth grade Elementary Schools: An Analysis within the Ki Hajar Dewantoro School Cluster, Semarang Regency - Laelatul Fadilah; Nimas Puspitasari; Puji Winarti (Educia Journal, 2026)
The successful implementation of Integrated Science and Social Studies (IPAS) learning in elementary schools is closely related to the availability and effective utilization of learning media that can facilitate students’ understanding of concepts and enhance their learning engagement. This study aimed to analyze the availability and utilization of IPAS learning media in Grade IV at public elementary schools within the Ki Hajar Dewantara Cluster, East Ungaran District, Semarang Regency. The study employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving Grade IV teachers and school principals from the selected schools. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of data condensation, data display, and conclusion drawing. The findings revealed that the availability of IPAS learning media was generally adequate and included printed media, visual media, concrete media, and digital media such as textbooks, maps, globes, science kits, anatomical models, laptops, LCD projectors, and learning videos. However, several media resources were still limited in quantity, requiring shared use among classes. Furthermore, teachers had utilized various learning media effectively in classroom instruction, particularly PowerPoint presentations, videos, pictures, maps, globes, and simple teaching aids. The use of these media increased students’ attention, motivation, participation, and conceptual understanding of IPAS content. The study concludes that both the availability and utilization of learning media play a significant role in supporting effective IPAS learning. Therefore, schools should enhance media provision and strengthen teachers’ competencies in integrating innovative learning media into classroom practices.